Integrating Human Aspects in Production Management IFIP TC5 / WG5.7 Proceedings of the International Conference on Human Aspects in Production Management 5-9 October 2003, Karlsruhe, Germany - Zülch, Gert; Jagdev, Harinder Singh; Stock, Patricia (IFIP Advances in Information and Communication Technology, 2005)
This book is composed of six parts, each focusing on a specific theme: Human Resource Planning; Human Aspects in the Digital Factory; Human Aspects in Production Planning & Control; Knowledge Management; Management of Distributed Work; and Service Engineering. The included papers were presented at the IFIP International Working Conference "Human Aspects in Production Management." Following this conference, the papers were extended by the authors and passed a peer review process. All professional and academic researchers in the field of production management will find this book essential.